2014
DOI: 10.4238/2014.september.29.15
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 gene polymorphism in hepatocellular carcinoma patients with hepatitis B and C viruses

Abstract: ABSTRACT. Hepatocellular carcinoma (HCC) is the fifth most common malignancy worldwide. In Egypt, the incidence of HCC has doubled over the last decade. Matrix metalloproteinase-9 (MMP-9) plays a key role in cancer invasion and metastasis by degrading the extracellular matrix and basement membrane barriers. A cytosine (C)/ thymidine (T) single nucleotide polymorphism at position -1562 in the MMP-9 promoter is reported to influence the expression of the MMP-9 gene. The association between MMP-9 gene polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…For example, this common genetic variant has been associated with an increased risk of prostate cancer [21], breast cancer [22], and hepatocellular carcinoma [23]. However, the results of our study did not point toward a major role of the MMP-9 −1562C/T polymorphism in the pathogenesis and clinical course of GC in Turkish subjects.…”
Section: Discussionmentioning
confidence: 51%
“…For example, this common genetic variant has been associated with an increased risk of prostate cancer [21], breast cancer [22], and hepatocellular carcinoma [23]. However, the results of our study did not point toward a major role of the MMP-9 −1562C/T polymorphism in the pathogenesis and clinical course of GC in Turkish subjects.…”
Section: Discussionmentioning
confidence: 51%
“…The last group of genes that have been studied on hepatocellular carcinoma in Africa are those involved in angiogenesis, including VEGF , MMP , RASSF1A , and RECK . In Egypt, Samamoudy et al ( 230 ) reported that patients with MMP9 (rs3918242) are at high risk of developing liver cancer while RECK (rs12814325) ( 231 ) could account for the disease progression and metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…A recognized hallmark of invasion is the proteolytic breakdown of the extracellular matrix (ECM) through dysregulation of the matrix metalloproteinase system (Hanahan and Weinberg, ; Bonnans et al, ). In addition to MMP‐9 (El Samanoudy et al, ), MMP‐2, MMP‐13, TIMP‐1 and TIMP‐3 are also involved (Altadill et al, ; Gu et al, ). Interestingly, their effects are not limited to degradation of the ECM.…”
Section: Introductionmentioning
confidence: 99%